2012
DOI: 10.1186/2045-7022-2-25
|View full text |Cite
|
Sign up to set email alerts
|

Food allergies in developing and emerging economies: need for comprehensive data on prevalence rates

Abstract: Although much is known today about the prevalence of food allergy in the developed world, there are serious knowledge gaps about the prevalence rates of food allergy in developing countries. Food allergy affects up to 6% of children and 4% of adults. Symptoms include urticaria, gastrointestinal distress, failure to thrive, anaphylaxis and even death. There are over 170 foods known to provoke allergic reactions. Of these, the most common foods responsible for inducing 90% of reported allergic reactions are pean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(103 citation statements)
references
References 55 publications
2
93
0
8
Order By: Relevance
“…El diagnóstico de alergia alimentaria puede confundirse con la intolerancia a la lactosa, tal como lo describen Lifschitz, et al (20), lo cual afecta la prevalencia de la primera. En países como China, India y Brasil, se han estimado tasas de prevalencia más bajas, no obstante, podría haber subregistro o subdiagnóstico (21). En Colombia, no se ha determinado la tasa específica a nivel nacional.…”
Section: Discussionunclassified
“…El diagnóstico de alergia alimentaria puede confundirse con la intolerancia a la lactosa, tal como lo describen Lifschitz, et al (20), lo cual afecta la prevalencia de la primera. En países como China, India y Brasil, se han estimado tasas de prevalencia más bajas, no obstante, podría haber subregistro o subdiagnóstico (21). En Colombia, no se ha determinado la tasa específica a nivel nacional.…”
Section: Discussionunclassified
“…25,26 Al-Rabia suggested that the peak prevalence was between 21-40 years of age, after which it decreased. 27 However, the available literature regarding adult allergies is limited in comparison to that of paediatric allergies.…”
Section: Allergic Rhinitis and Food Allergies In Adultsmentioning
confidence: 99%
“…Actualmente, en América Latina existen pocas investigaciones que exploren la epidemiología de la alergia alimentaria (80), por lo que poco se conoce de la frecuencia de la alergia a la leche de vaca y al huevo de gallina. Sin embargo, algunos estudios publicados principalmente en México (81,82) y Brasil (57,83) reportan que, aunque ambos alimentos son las fuentes más usuales de alérgenos, la frecuencia encontrada es menor que en Europa y Estados Unidos y que otras fuentes, como el maíz y algunas frutas y verduras, tienen una frecuencia similar de sensibilización que incluso es mayor en algunas ciudades.…”
Section: Consideraciones Para América Latinaunclassified